Quality popular newspapers: ethics and sensationalism in a new standard of interior Journalism in Santa Catarina - Brazil - Seligman, Laura (Brazilian journalism research, 2009)
The circulation decrease of newspapers printed in Brazil, which followed an international trend, became a unique phenomenon observed in the country. The resumption of the editorial success of this media occurred with the adoption of new features that concentrate content and form on the lower classes. In the state of Santa Catarina, a representative sample of newspapers from all over the state was examined. To do that, we used Content Analysis according to Krippendorff’s definitions (1990). What we can see is the establishment of a new standard of interior Journalism in Santa Catarina, with the content focused on what is now classified as Quality Popular Journalism. It is the preference for the local viewpoint and for service to the community that is intended, abandoning traditional characteristics of this segment such as sensationalism.